ANALISIS PENERAPAN VISUAL COACHING SEBAGAI PERUMUSAN GOAL SETTING PADA PENDAMPINGAN BISNIS STARTUP DIGITAL - Jacobus Wiwin Kuswinardi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
Digital startups face significant challenges in defining clear and structured goals to achieve sustainable business growth. One method that can be utilized in startup business mentoring is visual coaching, a visual-based approach that helps entrepreneurs understand, formulate, and implement their business goals more effectively. This study aims to analyze the application of visual coaching in the goal-setting process during digital startup business mentoring. The research employs a qualitative approach through case studies of several digital startups that have incorporated visual coaching into their mentoring sessions. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that visual coaching enhances startup founders' understanding of their business objectives in a more systematic and structured manner. The use of visual elements such as mind mapping, flowcharts, and infographics has proven to assist in developing clearer business strategies, increasing team engagement, and accelerating decision-making processes. Furthermore, the application of visual coaching positively impacts motivation and provides greater clarity in the startup's vision when facing business challenges. Therefore, visual coaching can be an effective approach in digital startup business mentoring, particularly in designing and establishing more concrete and measurable goals.